Uncertainty: At the core of general practice - Rortveit, Guri (Tidsskrift for Forskning i Sygdom og Samfund, 2018)
Uncertainty is a core concept of medical activity, especially in general practice, where illness is evaluated at an early stage and available diagnostic tools are limited. In this paper, theoretical aspects of the concept of uncertainty are used to analyze the handling of uncertainty in two areas of the health care system: clinical encounters in primary care and at the public health level. Wynne’s categorizations of risk, strict uncertainty, and ignorance represent one approach that may be useful in acknowledging when a situation is not suitable for an evidence-based approach. Similarly, the concept of post-normal science is valuable in describing situations where uncertainty prevails together with high stakes, values in dispute, and an urgent need for decision making. Accepting that science cannot always reduce uncertainty but it can, rather, be a tool for analyzing an uncertain situation as a prerequisite for attending to uncertainty in a productive way—even when the end results are unfavorable. This paper provides examples of uncertainty in both clinical and public health situations.